Early education curriculum a child's connection to the world - Jackman, Hilda L. (Australia Wadsworth Cengage Learning, 2012)
"The fifth edition of Early Education Curriculum: A Child's Connection To The World focuses on the process of planning and implementing a curriculum, and setting up an inclusive child-centered environment. Guided by new research, position statements, and developmentally appropriate practice, the book helps both prospective and experienced teachers make informed decisions about curriculum content. Now in full color, the book meets the needs of a diverse range of readers, helping them to develop creative thinking and the ability to effectively apply theory to an early childhood classroom setting."--Publisher's description.
Part One. Creating the environment that supports curriculum and connects children -- 1. Starting the process -- 2. Creating curriculum -- Part Two. Discovering and expanding the early education curriculum -- 3. Language and literacy -- 4. Literature -- 5. Math -- 6. Science -- 7. Social Studies -- 8. Art -- 9. Sensory centers -- 10. Music and movement -- 11. Puppets -- 12. Dramatic play and creative dramatics -- Appendix A. My self : integrated curriculum theme with activities -- Appendix B. Resources for teachers, with website listings -- Appendix C. Professional organizations -- Glossary.
Keywords: Early childhood education -- Curricula -- United States; Curriculum planning -- United States; Interdisciplinary approach in education -- United States; Early childhood education -- Activity programs -- United States